The interplay of perceptual processing demands and practice in modulating voluntary and involuntary motor responses - Marinovic, Welber; Nguyen, An; Vallence, A.M.; Tresilian, J.R.; Lipp, Ottmar (2024)
Understanding how sensory processing demands affect the ability to ignore task-irrelevant, loud auditory stimuli (LAS) during a task is key to performance in dynamic environments. For example, tennis players must ignore crowd noise to perform optimally. We investigated how practice affects this ability by examining the effects of delivering LASs during preparatory phase of an anticipatory timing (AT) task on the voluntary and reflexive responses in two conditions: lower and higher visual processing loads. Twenty-four participants (mean age = 23.1, 11 females) completed the experiment. The AT task involved synchronizing a finger abduction response with the last visual stimulus item in a sequence of four Gabor grating patches briefly flashed on screen. The lower demand condition involved only this task, and the higher demand condition required processing the orientations of the patches to report changes in the final stimulus item. Our results showed that higher visual processing demands affected the release of voluntary actions, particularly in the first block of trials. When the perceptual load was lower, responses were released earlier by the LAS compared to the high-load condition. Practice reduced these effects largely, but high perceptual load still led to earlier action release in the second block. In contrast, practice led to more apparent facilitation of eyeblink latency in the second block. These findings indicate that a simple perceptual load manipulation can impact the execution of voluntary motor actions, particularly for inexperienced participants. They also suggest distinct movement preparation influences on voluntary and involuntary actions triggered by acoustic stimuli.